1994
DOI: 10.1007/bf02059613
|View full text |Cite
|
Sign up to set email alerts
|

Responses of fig wasps to host plant volatile cues

Abstract: Fig wasps (Chalcidoidea; Agaonidae) are intimately associated with the 750 or so species of fig trees (Ficus, Moraceae). Each tree species is usually pollinated by a single species of wasp belonging to the subfamily Agaoninae, while other wasps of the family are parasitoids or seed predators. Previous experiments have shown that the wasps are attracted to the trees by volatiles emanating from the figs. Using fig-bearing trees and arrays of sticky traps baited with figs, we investigated the specificity of wasp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
4

Year Published

1995
1995
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 24 publications
0
53
0
4
Order By: Relevance
“…Pollinating wasps and pollination -Ficus eximia pollinators are attracted to figs when female flowers are receptive (female phase). Studies have demonstrated that pollinator attraction is mediated through volatile chemicals released from figs in the receptive phase (van-Noort et al 1989, Ware et al 1993, Hossaert-McKey et al 1994, Ware & Compton 1994. The pollinator of F. eximia penetrates the ostiole crawling through the bracts, and its wings and parts of antennae usually break off during this process.…”
Section: Resultsmentioning
confidence: 99%
“…Pollinating wasps and pollination -Ficus eximia pollinators are attracted to figs when female flowers are receptive (female phase). Studies have demonstrated that pollinator attraction is mediated through volatile chemicals released from figs in the receptive phase (van-Noort et al 1989, Ware et al 1993, Hossaert-McKey et al 1994, Ware & Compton 1994. The pollinator of F. eximia penetrates the ostiole crawling through the bracts, and its wings and parts of antennae usually break off during this process.…”
Section: Resultsmentioning
confidence: 99%
“…The attraction of specific floral volatiles to other atypical pollinators is understandable, as the specificity of floral volatiles is usually achieved by quantitative differences in relative proportions of many common compounds, and some compounds that actively attract certain pollinators may occur in volatiles of several plants [15]. This flexibility in host preference may also provide an explanation for the atypical pollinators captured in earlier trapping studies [30,47]. Floral volatiles between two sympatric figs, F. auriculata and F. oligodon, were notably similar and shared at least three pollinator species, with the highest pollinator sharing ratio being 34.88% (table 1; electronic supplementary material, table S5 and figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…This specialized inflorescence is known as a syconium, and it defines the genus Ficus. When a fig's syconia are receptive, they emit scents that attract the pollinator wasps (Ware and Compton 1994;Gibernau et al 1998;Grison-Pigè et al 2002). Pollen-bearing female wasps (foundresses) enter the syconium by the ostiole, which is the bract-lined opening situated at the apex of the syconium.…”
Section: Introductionmentioning
confidence: 96%